2006
DOI: 10.1037/0021-843x.15.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of metamemory deficits to schizophrenia.

Abstract: A number of recent studies have demonstrated that individuals with schizophrenia display knowledge corruption; that is, they hold false information with strong conviction. This aberration in metamemory is thought to stem from poor memory accuracy in conjunction with impaired discrimination of correct and incorrect judgments in terms of confidence. Thirty-one participants with schizophrenia, along with 61 healthy control participants and 48 control participants with other psychiatric conditions, participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 67 publications
6
80
0
3
Order By: Relevance
“…It has repeatedly been observed that the retrospective confidence judgments for incorrect answers expressed by patients with schizophrenia are higher than those of matched healthy participants (Danion et al, 2001a;Moritz and Woodward, 2006;Moritz et al, 2003;Moritz et al, 2005). In the meantime, the prospective metamemory judgments of patients with schizophrenia are lower than those of healthy participants (Bacon et al, 2001;Bacon et al, 2007;Souchay et al, 2006;Thuaire et al, 2012.…”
Section: Metamemory Monitoring In Patients With Schizophreniamentioning
confidence: 86%
“…It has repeatedly been observed that the retrospective confidence judgments for incorrect answers expressed by patients with schizophrenia are higher than those of matched healthy participants (Danion et al, 2001a;Moritz and Woodward, 2006;Moritz et al, 2003;Moritz et al, 2005). In the meantime, the prospective metamemory judgments of patients with schizophrenia are lower than those of healthy participants (Bacon et al, 2001;Bacon et al, 2007;Souchay et al, 2006;Thuaire et al, 2012.…”
Section: Metamemory Monitoring In Patients With Schizophreniamentioning
confidence: 86%
“…Following the seminal work of Garety and coworkers in the late 1980s (Garety et al 1991;Huq et al 1988), researchers have detected a number of cognitive biases in individuals with schizophrenia (Freeman 2007;Garety and Freeman 2013;Savulich et al 2012;van der Gaag 2006). For example, many patients display overconfidence in erroneous judgments (Moritz and Woodward 2006;Moritz et al 2003Moritz et al , 2012Peters et al 2007); have a bias against integrating disconfirmatory evidence (BADE; Speechley et al 2012); tend to over-rely on confirmatory evidence and reasoning heuristics (Balzan et al 2012b(Balzan et al , 2013; and perhaps most robustly, have been shown to exhibit a jumping to conclusions (JTC) bias (Balzan et al 2012a;Garety et al 2005;Lincoln et al 2010;Moritz and Woodward 2005). Although the pattern of results is not fully consistent across trials, there is also mounting evidence for attributional biases (Bentall et al 1994;Lincoln et al 2010;Mehl et al 2014).…”
Section: Introductionmentioning
confidence: 84%
“…It is suggested [4] that people with mental health problems in forensic services have often had little active involvement in their own care, for some the active collaborative approach, central to the success of the psychoeducational programme and subsequent evaluation, is very daunting and sometimes unwelcome. Added to the relational difficulties there is evidence to suggest that people suffering from a psychotic illness have defects of cognitive functions such as problem solving ability, explicit memory, knowledge and general intellectual capacities [40]. Arguably results of the magnitude of intellectual deficit in patients with psychosis do not show a clear pattern [41].…”
Section: Discussionmentioning
confidence: 99%